An analytical modeling with experimental validation of bone temperature rise in drilling process. (October 2020) - Amewoui, Foli; Le Coz, Gaël; Bonnet, Anne-Sophie; Moufki, Abdelhadi
Highlights: A simple analytical model allows predicting temperature rise during bone drilling, as a function of spindle speed. The lateral friction during bone drilling plays a significant role in the duration of the temperature increase inside bone. It is unsuitable to consider bone as an infinite medium inside thermal models, to reproduce temperature rise during drilling.. Abstract: Predicting the bone thermal response in a surgical operation remains a major challenge. In the previous works, metal machining theory has frequently been used to predict bone temperature in drilling process. However, several experimental studies demonstrate that the chip formation process is very complex compared to metal cutting. In the present study, a simplified analytical model based on the moving heat source approach combined with the method of image sources is developed. The heat source due to the drill-bit tip was supposed to be proportional to the cutting energy. The friction at the tool-hole contact was also considered. An experimental study was performed on fresh femur pig bone for cutting speeds from 2 to 20 m/min . Temperature rise, drilling forces and bone volume fraction were measured. The experimental validation showed that the model reproduces satisfactorily the increase in temperature up to the maximum value while it overestimates the temperature during the cooling stage. A parametric study (thermal boundary conditions, lateral friction) was also performed. From the predicted results, it appears that the model can be improved by considering the effects of the bone volume fraction which can present a significant variation in the bone sample.